To solve the polynomial equation \( 2x^5 - 4x^3 + 2x = 0 \), we can start by factoring the polynomial.
- Factor out the common term: Notice that all terms in the polynomial have a common factor of \( 2x \).
\[ 2x^5 - 4x^3 + 2x = 2x(x^4 - 2x^2 + 1) \]
-
Factor the quadratic: Now we need to factor \( x^4 - 2x^2 + 1 \). This can be recognized as a quadratic in terms of \( x^2 \). We can set \( y = x^2 \): \[ y^2 - 2y + 1 = (y - 1)^2 = (x^2 - 1)^2 \]
-
Combine the factors: Therefore, \[ x^4 - 2x^2 + 1 = (x^2 - 1)^2 = (x - 1)^2(x + 1)^2 \]
-
Complete factorization: Now, we combine all the factors: \[ 2x(x - 1)^2(x + 1)^2 = 0 \]
-
Solve for roots: Setting each factor to zero gives us:
- From \( 2x = 0 \): \( x = 0 \)
- From \( (x - 1)^2 = 0 \): \( x = 1 \) (with multiplicity 2)
- From \( (x + 1)^2 = 0 \): \( x = -1 \) (with multiplicity 2)
Thus, the roots of the polynomial equation are \( x = 0 \), \( x = 1 \), and \( x = -1 \).
In terms of the choices given, the correct solution is:
c. x = -1, x = 0, x = 1